Chapter Mapping Jewish Identities Migratory Histories and the Transnational Re-Framing of 'Ashkenazi BRCA Mutations' in the UK and Brazil - Mozersky, Jessica (Taylor & Francis, 2014)
Through a comparion of etnographic research in the UK and Brazil, this chapter has examined now changing scientific and medical understandings regarding the origin, genealogical history and patrimony of the so-called Ashkenazi mutations have been diversely taken up and put to use in clinical/research contexts. It has explored the very differing differing differing consequences this can have for the way health care practitioners, scientists, patients and their families engage with and incorporate knowledge about hereditary BRCA mutations into scientific narratives, clinical practices and understandings of clinical/familial risk and identity.